2018
DOI: 10.21767/2471-8564.100004
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Post Procedural Pain and Opioid Consumption Using IV Acetaminophen and IV Ibuprofen Following Uterine Fibroid Embolization: A Prospective, Doubleblind, Randomized Controlled Study

Abstract: Purpose: Uterine fibroid embolization (UFE) is associated with post-procedural pain and nausea. In this double-blind randomized controlled study, we compared pre-procedure intravenous (IV) acetaminophen/ibuprofen to postprocedure IV ketorolac in UFE patients. Methods:After institutional review board approval, UFE candidates 21-60 years old were screened and randomly assigned to one of four arms: acetaminophen (1 g), ibuprofen (800 mg), acetaminophen (1 g) and ibuprofen (800 mg) combined, and an active comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The study showed that the IV acetaminophen þ ibuprofen group provided similar pain control with less opiate use compared with the ketorolac group (28.09 mg compared with 40.33 mg of morphine equivalents); however, there was more nausea experienced in the IV acetaminophen/ibuprofen group. 41 Discharge Medications Discharge medications rely on over-the-counter options such as NSAIDs and acetaminophen with the addition of oral opiate analgesia (oxycodone 5 mg/acetaminophen 325 mg) for break through pain. Antiemetics and stool softeners are also commonly provided.…”
Section: Nonopiate Analgesiamentioning
confidence: 99%
“…The study showed that the IV acetaminophen þ ibuprofen group provided similar pain control with less opiate use compared with the ketorolac group (28.09 mg compared with 40.33 mg of morphine equivalents); however, there was more nausea experienced in the IV acetaminophen/ibuprofen group. 41 Discharge Medications Discharge medications rely on over-the-counter options such as NSAIDs and acetaminophen with the addition of oral opiate analgesia (oxycodone 5 mg/acetaminophen 325 mg) for break through pain. Antiemetics and stool softeners are also commonly provided.…”
Section: Nonopiate Analgesiamentioning
confidence: 99%